Activation of cannabinoid receptor 2 protects rat hippocampal neurons against Aβ-induced neuronal toxicity. (14th September 2020) - Zhao, Jingfu; Wang, Mengzhen; Liu, Wei; Ma, Zegang; Wu, Jie
Highlights: Chronic treatment with Aβ1-42 oligomers for 7 days induces hippocampal neuronal toxicity and upregulated cannabinoid receptor 2 (CB2 R). Activation of CB2 Rs by agonist (JWH133) prevents Aβ1-42 -induced neurotoxicity. Activation of CB2 Rs enhances Akt signaling that is involved in CB2 R's neuronal protective effects. Abstract: Alzheimer's disease (AD) is a dementing, neurodegenerative disorder characterized by increased accumulation of beta-amyloid peptides (Aβ), degeneration of hippocampal neurons and the gradual development of learning and memory deficits. Therapeutically, there are still no ideal medicines available and this represents an urgent need for the development of new strategies to treat AD. Emerging lines of evidence suggest that modulation of the cannabinoid system exhibits neuroprotective effects in various neurological diseases, including AD. However, a consensus is yet to emerge as to the impact of hippocampal cannabinoid receptor 2 (CB2 R) in protection of hippocampal neurons against Aβ induced neuronal toxicity. Here, we report that chronic treatment of primary hippocampal neuronal cultures with 100 nM Aβ1–42 oligomers for 7 days results in neurotoxicity, which includes increases in lactate dehydrogenase (LDH) levels, suggesting an Aβ1–42 –induced neuron apoptosis. Further, chronic Aβ1–42 reduces the ratio of phosphorylated Akt (pAkt)/Akt, in turn decreases neuronal Bcl-2/Bax ratio, and leads to an increase of caspase-3, which likely underlines the signal pathway of chronic Aβ1–42 –induced neuron apoptosis. Interestingly, pre-treatments of CB2 R agonist (JWH133, 10 μM) with Aβ1–42 prevents Aβ1–42 -induced the decrease of pAkt/Akt ratio, the decrease of Bcl-2/Bax ratio, and the increase of caspase-3, and protects hippocampal neurons against Aβ1–42 -induced apoptosis. All neuroprotective effects of JWH133 are abolished by a selective CB2 R antagonist, AM630. Taken together, the activation of hippocampal CB2 Rs protects neurons against Aβ1–42 toxicity, and the CB2 R-mediated enhancement of the pAkt signaling is likely involved in the protection of hippocampal neurons against Aβ1–42 -induced neuronal toxicity.